FAKTOR-FAKTOR YANG MEMPENGARUHI FIRM VALUE (STUDI PERUSAHAAN BARANG KONSUMSI) - Richard Felix; Viriany Viriany (Fakultas Ekonomi, Universitas Tarumanagara, 2026)
This study is conducted to obtain empirical evidence about the influence of Firm Size, Profitability, and Leverage on Firm Value of Consumer Goods sub sector company listed on the Indonesia Stock Exchange during 2019- 2021 based on Jakarta Stock Industrial Classification (JASICA). The sampling method of this study is purposive sampling to obtains 19 Consumer Goods Company to obtain 57 data. Analysis techniques used in this study is moderated regression analysis (MRA). This study used Eviews 12 SV to analyze panel data of this study. The results showed that Profitability significantly affected Firm Value, But Firm Size and Leverage have significantly negative effect and did not affect Firm Value. The implication of this study are the need to increase the effectiveness of assets owned by the companies and the need of company management ability to manage the debt owned that will will bring a positive signal for investors.